Populational genetic structure and sociogenetic structure of cocoon masses of Digelasinus diversipes (Kirby, 1882) (Hymenoptera: Symphyta: Argidae) - Daniele Boraschi; Marco Antonio Del Lama (Genetics and Molecular Biology, 2004)
Gene variation and population genetic structure of the Neotropical sawfly Digelasinus diversipes were measured by allozyme analyses using starch gel electrophoresis. Cocoon masses were collected in Eugenia glazioviana (Myrtaceae) stems, in two areas of the "Estação Ecológica Jataí" (Luiz Antônio, SP, Brazil - 21°25' S, 47°50' W), in 2000 and 2001. The average heterozygosity observed in this species (Hobs = 0.094 ± 0.025) was not significantly different from other Symphyta groups; it was, however, significantly higher than in other Hymenoptera populations. No significant levels of inbreeding were found (F IS = 0.062; chi2 = 29.9; p > 0.05), but the population was subdivided (F ST = 0.070; chi2 = 458.9; p < 0.05), suggesting the absence of a significant gene flow among the samples studied, due to limited dispersion ability. The low relatedness coefficients found (ranging from 0.23 ± 0.09 to 0.44 ± 0.10) suggest that larvae from different ovipositions associate to construct the cocoon masses.